THE EFFECT OF pH ON THE ADSORPTION OF MICRONUTRIENT CATIONS OF Ca 2+ AND K + BY SILICA FROM LAPINDO MUD - Ikhsan, Jaslin; Sulastri, Siti; Priyambodo, Erfan (Jurnal Penelitian Saintek, 2015)
The aim of this research was to determine the effect of pH on the adsorption of micronu- trients of Ca 2+ and K . by silica from lapindo mud. Data were collected by the adsorption experiments, on which 3 grams of silica separated from Lapindo mudwere dissolved in 300 mL of 0.0001 or 0.001 M Ca + 2+ or K ., and stirred for 2 hours. The pH of suspension was varied and left for equilibrate for 2 hours, and a sample was taken and measured for free concentration of K + + .cation using Flame Atomic Emission Spectroscopy and of Ca using Atomic Absorption Spectroscopy (AAS). The pH ranges were from 3 to 10. Temperature o 30 C and contact time of 2 hours were maintained. The research showed that both cations were adsorbed in sigmoid curve, increased with increasing pH values. In entire ranges of observed pH, the percentage of cations adsorbed by silica was not different signiï¬ cantly. The adsorbent of silica formed silanol (SiOH) in water. The –OH groups of silica were protonated forming SiOH o at lower pH and deprotonated forming SiO¯ at higher pH. Wether Ca 2+ or K + 2 + . cations were bound to silica surfacesvia cation exchange reactions, on which Ca2+ or K + . exchanged H of SiOH using one charge of the cations, forming [SiO(CaO)] for Ca 2+ , and [SiO-K] for K